Bearly Guilty: Understanding Human–Andean Bear Conflict Regarding Crop Losses - Albarracín, Viviana; Aliaga-Rossel, Enzo (Ethnobiology Letters, 2018)
Conflicts between wildlife and humans are increasing worldwide, especially in areas where they coexist and share resources. To investigate attitudes and opinions of the human population towards human-Andean bear (Tremarctos ornatus) conflicts in two indigenous Aymara communities, Chuñavi and Lambate, Bolivia, semi-structured interviews were directed to an adult member of families in the communities. Simultaneously, we registered, monitored, and evaluated 70 farm plots to record evidence of Andean bear and other wildlife damage to the maize crops and plants. We found that the locals thought the bear caused the most damage when, in actuality, the most harmful issues identified for maize crops were environmental factors, followed by parrots and birds. Knowledge of the interactions between wild animals and productive systems can contribute to an understanding of Andean bear-human coexistence.